Women and the Hospitaller Order on Rhodes and Cyprus in the fourteenth and fifteenth centuries - Coureas, Nicholas Savvas (Ordines Militares Colloquia Torunensia Historica. Yearbook for the Study of the Military Orders, 2022)
The women on Hospitallers Rhodes were by no means a uniform group. They differed in terms of social class, some being slaves, others being serfs while others were free women, at times wealthy property owners. Nor did the women on Rhodes have the same ethnicity. While the majority of women were Greek, like the inhabitants of Rhodes in general, not all of them originated from Rhodes. In addition, there were also women of Syrian origin, as well as women of Latin and Jewish origin. In terms of marital status, there were unmarried women, married women and widows, and in terms of legal standing there were lay women but also women in religious orders, nuns or donors. In spatial terms some women resided in the countryside while others lived in the Town of Rhodes. Members of all the groups of women mentioned above had contacts or relations with the Hospitaller Order and its members, and women feature in the legislation of the Order.